Risk Factors For Malaria Incidence In Pregnant Women In Puskemas Bosnik And Marau Regency Biak Numfor - Inggrit Rita Uli Manik; Ritha Rumansara; Ruslan . (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
Malaria infection in pregnancy is very detrimental to both the mother and the fetus it contains, because it can increase the morbidity and mortality of the mother and fetus. The prevalence of malaria in Papua Province with Annual Parasite Incendence in 2016 amounted to 208.95 per thousand population, the prevalence of malaria in pregnant women in Papua Province as much as (3.09%). The prevalence of malaria in pregnant women in Biak Numfor Regency in 2017 was 4.11%. The purpose of this study was to determine the risk factors for the incidence of malaria in pregnant women at the Bosnik and Marau Health Centers, Biak Numfor Regency in 2018.This study is an observational study with case control design in pregnant women in the Bosnik Health Center and Marauw Health Center area of Biak Numfor Regency. The study sample with simple random sampling was 27 pregnant women as cases and 27 pregnant women as control.data analised with chi square test. From the results of a multivariate analysis found 2 (two) variables associated with malaria incidence in pregnant women, namely sleeping not using mosquito nets (OR = 3,768 p = 0.024 95% CI 1,158-12,270) and Hb anemia < 9 gr% (OR = 5,500 p = 0.013 95% CI 1,323-22,862) while 3 (three) variables namely low economic status, first parity and ? 4 and nutritional status is not associated with malaria incidence. Risk factors for malaria incidence in pregnant women are related to sleep habits not using mosquito nets and anemia Hb < 9gr%.